Analysis of the impact of PACS implementation on the efficiency of radiology service workflow - Wenda Anastasia Indriyani; Akhirida Putri (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
The development of information technology in radiology, especially with the implementation of the Picture Archiving and Communication System (PACS), has brought significant changes in the workflow of medical imaging. This study uses a descriptive qualitative research design to analyze the impact of PACS implementation on workflow efficiency in the Radiology department of Wahidin Sudirohusodo Hospital Makassar. The results showed that the implementation of PACS impacted five main variables: Time Efficiency, Data Input Errors, Data Accessibility and Use, Job Satisfaction, and Filmless Reduction, which was analyzed using a p-value statistical test with a significance value of <0.05. From these results, it can be concluded that the implementation of the system provides improvements in various aspects measured, especially efficiency, accuracy, accessibility, and satisfaction.